2022
DOI: 10.3389/fmars.2022.1028717
|View full text |Cite
|
Sign up to set email alerts
|

Variation in mesopelagic fish community composition and structure between Mediterranean and Atlantic waters around the Iberian Peninsula

Abstract: Mesopelagic fish populations are characterised by high species richness and abundance, and have been identified as important contributors to the active carbon fluxes in the open ocean. We report variability in communities of mesopelagic fish between five zones around the Iberian Peninsula, i.e. Balears and Alboran in the Mediterranean, and Cadiz, Lisboa and Galicia in the Atlantic. Day and night samples were collected from 7 layers of the water column with a midwater trawl fitted with a multisampler. Temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 77 publications
2
5
0
Order By: Relevance
“…All the remaining species were found to migrate. The most abundant species found in the upper layer during the night were C. maderensis, H. benoiti and B. glaciale, in line with what has been previously evidenced in the W. Mediterranean 22,24 . Additionally, although large numbers of individuals of M. punctatum were observed on the sea surface at night (and caught with a landing net; authors' pers.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…All the remaining species were found to migrate. The most abundant species found in the upper layer during the night were C. maderensis, H. benoiti and B. glaciale, in line with what has been previously evidenced in the W. Mediterranean 22,24 . Additionally, although large numbers of individuals of M. punctatum were observed on the sea surface at night (and caught with a landing net; authors' pers.…”
Section: Discussionsupporting
confidence: 89%
“…The current work presents the results of the rst acoustic survey aiming to study DSLs and their composition, not only in the Gulf of Corinth, but also in the Central Mediterranean Sea. The shes diversity of the mesopelagic zone in the study area is relatively low, as has been previously reported for the Mediterranean 10,15,24 where the presence of many deep-water species inhabiting the adjacent eastern Atlantic seems to be constrained by (i) the relatively shallow strait (Gibraltar) connecting the two Seas and (ii) the high temperature in the deep waters of the Mediterranean compared to the colder Atlantic 22,38 . In addition, no Mediterranean members of the Gonostomatidae and Phosichthyidae families (e.g.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…13.5 • C and salinity ca. 38.5, below 200 m) [65]. The feeding habits of these species in the western Mediterranean (off the Balearic Islands and the Gulf of Lions) and the northeastern Atlantic (e.g., the northern Mid-Atlantic Ridge, Azores, and the Canary Islands) have been studied through the analysis of stomach contents and stable isotopes at the species and community levels, e.g., [17,42,43,[66][67][68][69][70].…”
Section: Introductionmentioning
confidence: 99%